Corrections to “An In-Laboratory Comparison of FocusBand EEG Device and Textile Electrodes Against a Medical-Grade System and Wet Gel Electrodes” - Matias Rusanen; Sami Myllymaa; Laura Kalevo; Katja Myllymaa; Juha Toyras; Timo Leppanen; Samu Kainulainen (IEEE Access, 2023)
In the above article [1], Table 2 partially showed erroneous values for the absolute skin-electrode impedances while the correct median absolute impedances were presented in Figure 2. The authors regret the error and apologize for the possible inconvenience. The corrected Table 2 is presented below.